Show, Tell, Bridge : Pop - up Storytelling in the community - Howarth, Lynne; Quirke, Lisa (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2018)
This proposed poster reports on "pop - up" object - narrative sessions within two community - focused farmers' markets in Toronto, Canada, and the data gathered for current research on the affordance of objects in negotiating individual and group identity. How do we impart information about ourselves in reference to common everyday objects, and through stories about a favourite vegetable? Findings from the study will inform the design of programmatic guidelines for objects and storytelling within a community setting.